Rendimiento académico: ¿qué papel juegan los factores institucionales? (2014)
This paper examines which is the relationship between institutional factors and the academic achievement in mathematics. To reach this purpose, 1,653 students who had taken the test in 2010 and who came from 44 high schools in Medellin, Colombia were selected. The econometric estimate was conducted by means of Hierarchical Linear Model (HLM), which its independent variables were classified in two levels: student and institution. Our main results provide evidence to support that 31.4% of educational attainment in mathematics is explained by institutional variables such as the number of hours in math class, to belong to private schools and with a unique gender, the use of textbook and the school size.